Takotsubo syndrome in a teen health centre. (18th March 2019) - Alcaraz-Mor, R; Gasche, E; Villa, A; Lehucher-Michel, M.-P
Abstract: Background: Takotsubo syndrome is also referred to as stress cardiomyopathy and typically occurs in females aged 55 years and older. This demographic represents a significant part of the healthcare workforce and they have over recent decades experienced increasing levels of violence from patients and clients. Aims: Our study describes a Takotsubo syndrome that occurred following an incident of physical and verbal aggression at work in a teen health centre. Case report: We report the case of a 56-year-old female community educator who suffered chest pain 48 h after suffering an aggressive incident at work. She had no history of cardiovascular disease. During hospitalization she was investigated with an electrocardiogram, echocardiography, coronary angiography, left ventriculography and a cardiac magnetic resonance imaging. Examinations confirmed the diagnosis of Takotsubo cardiomyopathy. This was deemed to be a work-related accident. With the help of her occupational physician, the patient was able to return to work with work adjustments. Conclusions: Increasing levels of violent behaviours towards staff in the health care sector underscores the need for measures in the workplace to help prevent precipitation of this syndrome in workers.